Carfilzomib-dexamethasone versus bortezomib-dexamethasone in relapsed or refractory multiple myeloma: updated overall survival, safety, and subgroups - Orlowski, Robert Z.; Moreau, Philippe; Niesvizky, Ruben; Ludwig, Heinz; Oriol, Albert; Chng, Wee Joo; Goldschmidt, Hartmut; Yang, Zhao; Kimball, Amy S.; Dimopoulos, Meletios A. (Clinical lymphoma, myeloma & leukemia, 2019)
Introduction - The phase III RandomizEd, OpeN Label, Phase 3 Study of Carfilzomib Plus DExamethAsone Vs Bortezomib Plus DexamethasOne in Patients With Relapsed Multiple Myeloma (ENDEAVOR) trial showed significantly improved progression-free survival and overall survival (OS) with carfilzomib (56 mg/m2) and dexamethasone (Kd56) versus bortezomib and Kd56 (Vd) in patients with relapsed or refractory multiple myeloma (RRMM). We report updated OS and safety data after 6 months of additional follow-up. - Patients and Methods - Patients with RRMM (1-3 previous lines of therapy) were randomized 1:1 to Kd56 or Vd. Median OS was estimated using the Kaplan-Meier method; OS was compared between treatment groups using Cox proportional hazards models. - Results - As of July 19, 2017, median follow-up was 44.3 months for Kd56 and 43.7 months for Vd. Median OS was 47.8 months (Kd56) versus 38.8 months (Vd; hazard ratio, 0.76; 95% confidence interval, 0.633-0.915). OS was longer with Kd56 versus Vd within age and cytogenetic subgroups, and according to number of previous lines of therapy, previous bortezomib exposure, previous lenalidomide exposure, and lenalidomide-refractory status. Exposure-adjusted incidences per 100 patient-years of adverse events (AEs) were 1352.07 for Kd56 and 1754.86 for Vd; for Grade ≥3 AEs, these values were 162.31 and 175.90. - Conclusion - With median follow-up of approximately 44 months, clinically meaningful improvements in OS were observed with Kd56 versus Vd, including in all subgroups examined. The Kd56 safety profile was consistent with previous analyses.